Current and emerging immunotherapeutic approaches to the treatment of multiple myeloma - Dawn Swan; Kevin Lynch; Mark Gurney; Michael O’Dwyer (Therapeutic Advances in Hematology, 2019)
Multiple myeloma (MM) has a worldwide incidence of 1–5/100,000/year. Outcomes have improved significantly in recent years following incorporation of immunomodulatory drugs and proteasome inhibitors into standard-of-care regimes. MM is profoundly immunosuppressive, enabling immune evasion, proliferation and disease progression. The role of the immune system in MM is becoming increasingly characterized and understood, and numerous therapies are under development or in routine clinical use targeting these elements of MM pathogenesis. In this review we discuss the immunosuppressive effects of MM, then the therapies targeting these defects. Specifically, we review the monoclonal and bispecific antibodies, alongside adoptive cellular therapies currently under investigation.